2014
DOI: 10.1002/ejic.201400085
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Solvent‐Exchange‐Driven Transformations in Multifunctional Coordination Polymers Based on Copper‐Containing Organosulfur Ligands

Abstract: The preparation by simple direct synthesis of a series of coordination polymers based on copper with chloride or bromide and dipyrimidinedisulfide is reported. The structural characterisations of these compounds reveal a rich structural variety as a result of the number of coordination modes available to the organosulfur ligand, in combination with the bridging capabilities of the halides. Interestingly, some of the polymers displayed fully reversible solvent exchange/removal crystal‐to‐crystal 2D to 0D and 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…40,41 On the other hand, in 1D coordination polymers (1D-CP), the solvent affects the way the CP is arranged, changing its supramolecular architecture 42 or allowing its application as sensors of metal ions 43 by facilitating the exchange of cation, anion and ligands. 44,45 Moreover, this inspired computational scientists to try to simulate the effect of the solvent on supramolecular assemblies. For example, S. Bandyopadhyay et al computationally investigated the solvent's role in ligand recognition.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 On the other hand, in 1D coordination polymers (1D-CP), the solvent affects the way the CP is arranged, changing its supramolecular architecture 42 or allowing its application as sensors of metal ions 43 by facilitating the exchange of cation, anion and ligands. 44,45 Moreover, this inspired computational scientists to try to simulate the effect of the solvent on supramolecular assemblies. For example, S. Bandyopadhyay et al computationally investigated the solvent's role in ligand recognition.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] However, design and structure prediction still remains a challenge. Despite the fact that there are some examples of CuIJI) halide coordination polymers based on ligands which contain at the same time hard N and soft S donor atoms, 5,[41][42][43][44][45] or organosulfur ligands and acetonitrile, 46,47 to the best of our knowledge, the combination of organosulfur and N-heteroaromatic ligands to obtain CuIJI) halide coordination polymers still remains unexplored. Introduction of N,N′ditopic ligands, such as 4,4′-bipyridine and pyrazine, to the CuX-thioacetamide system might lead to new compounds with intriguing structures and improved electrical and luminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that these small changes on metal•••metal distances can play a key role on the electrical and optical behavior of these semiconducting materials. 16,[22][23][24][25][26][27]…”
Section: Crystal Structuresmentioning
confidence: 99%